Relationship between prenatal coverage, maternal, pregnancy and APGAR characteristics of live newborn in Minas Gerais (Research, Society and Development, 2022)
The newborn's health is directly influenced by multiple maternal factors, such as physical, emotional, economic and social changes, maternal age, type of pregnancy, previous illnesses and number of consultations. Thus, prenatal care consists of preventive, diagnostic, curative and health-promoting actions for the pregnant woman and for the child. The aim of the article is to show the relationship between prenatal coverage, maternal and pregnancy characteristics and the APGAR of live births. This is a descriptive cross-sectional epidemiological study with data obtained through DATASUS to obtain information about live births in the state of Minas Gerais. The study shows that age and maternal education influence the number of prenatal consultations, and birth weight and the APGAR are related to the effectiveness of the assistance obtained in the consultations. It is concluded, therefore, that the effectiveness of prenatal care is essential to prevent and promote health for the mother and baby, and should follow the frequency recommendations proposed by the Ministry of Health to reduce maternal and child morbidity and improve satisfaction maternal and perinatal outcomes, in addition to increasing the baby's chances of having an adequate APGAR.